Run for Your Life: Embodied Environmental Story-Telling and Citizenship on the Road to Paris - Kaijser, Anna; Lövbrand, Eva (Frontiers in Communication, 2019)
In December 2015 the United Nations held its 21st climate change conference (COP21) in Paris. While political leaders convened to negotiate a new climate treaty, a diverse landscape of social movements, grassroots organizations, activists and artists assembled to mobilize public support for climate justice. In this paper we draw attention to one example of such non-traditional climate mobilization: Run for Your Life, organized by the Swedish theatre company Riksteatern. Framed as a ‘climate performance’, this initiative enrolled thousands of people to run distances in a relay race for climate justice, starting in Arctic Sweden and arriving in Paris on the first day of COP21. Public events were organized along the way, and the entire race was video recorded and broadcasted online. When signing up, runners were asked to submit their own climate story. Drawing on this archive of personal stories, we examine how Run for Your Life mobilized citizen engagement for climate justice. By paying attention to the multiple ways in which climate change is storied into people’s lives, we seek to understand why citizens decide to take climate action and which subject positions are available to them in the broader environmental drama. While the scripting of climate change as a planetary emergency perpetuated by global injustices serves an important function in the politics of climate change, we argue that it is in situated stories of environmental connection that climate change gains personal meaning. Here, kinship and solidarity are articulated, opening up for progressive social change.